Internal Carotid Artery Fibromuscular Dysplasia in a Child: Incidental Postmortem Finding after Head Injury - Arulselvi Subramanian (Journal of Laboratory Physicians, 2017)
Fibromuscular dysplasia (FMD) is a rare, segmental, nonatheromatous, and noninflammatory arterial disease of unknown etiology. It predominantly involves renal artery (60–75%) followed by extracranial part of the internal carotid artery and vertebral arteries (25–30%). The disease typically affects middle-aged women and involves intermediate-sized arteries throughout the body. There are rare case reports of extracranial FMD compounding a trauma case. A patient was brought to trauma center emergency with a history of fall from height. There were one previous episode of seizure and two episodes of vomiting. His Glasgow Coma Scale on admission was E1V1M4. Noncontrast computed tomography of the head showed fracture on the right zygomatic, temporal, and parietal bone, with underlying thin subdural hemorrhage. The patient underwent left frontotemporoparietal decompressive craniectomy and lax duraplasty with bone flap in bone bank. On the 1st postoperative day, he succumbed to his injuries despite timely surgery and necessary interventions. It was only postmortem when FMD was diagnosed in carotid artery by histopathological examination. On microscopy, intimal changes were seen in the form of expansion of subendothelial loose matrix with mesenchymal cells, thickening and hyalinization of the internal elastic lamina, areas of duplication and disruption of internal elastic lamina. Medial wall changes included thickening of the wall, focal loss of the smooth muscle, and replacement with fibrosis (dysplastic change). This case emphasizes the importance of considering this disease in the differential diagnosis of children and young adults with stroke (which subsequently lead to his fall).